Competitiveness in Latin America â€“ A study from Porterâ€™s model - da Silva, Ana Valeria Barbosa (2016)
This article aims to explore Porterâ€™s National Diamond model. It begins with a critical analysis of the competitiveness concept applied by Porterâ€™s model. Starting from the competitiveness model we are able to explore the four components that give shape to the Diamond and also to critically evaluate Porterâ€™s model in order to understand itâ€™s limitations. After that we analized the existing ranking models of countries and cities using the GCI â€“ Global competitiveness index, the WCY â€“ World Competitiveness Yearbook, and the ICUR â€“ Urban Competitiveness Index, checking how those three rankings grip to Porterâ€™s model. At last we analized the most outstanding factors â€œof successâ€ or â€œfailureâ€ in Latin American cities.